2006
DOI: 10.1093/jxb/erj136
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical responses of fruit exocarp of tomato (Lycopersicon esculentum Mill.) mutants to natural photo-oxidative conditions

Abstract: Photo-oxidative stress was imposed under natural solar radiation on exposed and shaded sections of detached fruit of immature green tomato (Lycopersicon esculentum Miller = Solanum lycopersicum L.) mutants (anthocyanin absent, beta-carotene, Delta, and high pigment-1) and their nearly isogenic parents ('Ailsa Craig' and 'Rutgers'). After 5 h exposure to high solar irradiance, either with or without ultraviolet (UV) radiation, surface colour changes, pigment composition, photosynthetic efficiency, antioxidant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 112 publications
9
53
0
Order By: Relevance
“…Chlorophyll fluorescence has been a non-destructive tool widely used to evaluate abiotic and biotic stress in tissue containing chlorophyll, that is, leaves and fruit (Seo et al, 2008). Previous studies have demonstrated that the photochemical efficiency of photosystem II (Fv/Fm) decreases on the peel of apple and tomato fruit exposed to sun damage (Torres et al, 2006;Naschitz et al, 2015), which concurs with the results obtained in the present study (Figure 7). Information to date indicates that this as a consequence of chlorophyll loss in sun-exposed tissue and the malfunction of the photosystem II reaction center when the fruit peel displays damage (Naschitz et al, 2015).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Chlorophyll fluorescence has been a non-destructive tool widely used to evaluate abiotic and biotic stress in tissue containing chlorophyll, that is, leaves and fruit (Seo et al, 2008). Previous studies have demonstrated that the photochemical efficiency of photosystem II (Fv/Fm) decreases on the peel of apple and tomato fruit exposed to sun damage (Torres et al, 2006;Naschitz et al, 2015), which concurs with the results obtained in the present study (Figure 7). Information to date indicates that this as a consequence of chlorophyll loss in sun-exposed tissue and the malfunction of the photosystem II reaction center when the fruit peel displays damage (Naschitz et al, 2015).…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, a correlation between photo-inhibition and the decreased Fv/Fm relationship has been observed (Torres et al, 2006). We found that Fv/Fm significantly decreased with the number of hours fruit were exposed to the sun (picked from the tree) at full sun, which was mitigated by using netting (Figures 8 and 9).…”
Section: Discussionmentioning
confidence: 59%
“…Three degrees of sunburn may occur: (1) photooxidative sunburn, in which fruits become photobleached by excessive levels of light (due to sudden changes in light conditions within the canopy); (2) sunburn browning, which is caused by changes in the light environment and enhanced temperatures and is associated with the severe degradation of chlorophylls and carotenoids; and (3) sunburn necrosis, which is associated with even higher temperatures that destroy tissues on the sun-exposed side of the fruit by causing a loss in cell integrity and cell leakage (Torres et al, 2006;Racsko and Schrader, 2012). Protection against sunburn includes developing sufficient leaf cover in the canopy to shade the fruit, activating the xanthophyll cycle-dependent excess energy dissipation system, and providing effective antioxidant protection through low-molecular-weight antioxidants, such as carotenoids, tocopherols, ascorbate, glutathione, and flavonoids, and by effectively using the ascorbateglutathione cycle and other enzymatic antioxidants (Torres et al, 2006;Chen et al, 2008;Zhang et al, 2015).…”
Section: Photooxidative Stress In Leaves Flowers and Fruitsmentioning
confidence: 99%
“…These changes in the physical structure of epicuticular wax will enhance water loss from berries as crystalline form of wax serves as a formidable barrier to water permeability than amorphous wax [64] accounting for the weight (volume) loss in sunburned berries. Moreover, sunburned berries had reduced color development similar to tomato fruit [65] indicating that sunburn inhibited color by degrading anthocyanin, which occurs when mRNA transcription of anthocyanins biosynthetic genes is inhibited [66]. By contrast, sunburn caused brown lesions in white grape varieties [23] attributable to cell death in the epidermal layers of the exocarp [67].…”
Section: Sunburnmentioning
confidence: 99%